Electricity for all - a driver for development in Africa? - Jörg Peters (RWI - Leibniz-Institut für Wirtschaftsforschung, 2017)
Large-scale investments in grid roll out to rural Africa have only a weak impact on income, health and education; benefits do not reach the poor. - More than 1.1 billion people in developing countries lack access to electricity. Based on the assumption that electricity is a prerequisite for economic development, the UN has proclaimed the goal of providing electricity to all by 2030. This will cost an estimated 640 billion USD. New empirical evidence, however, shows: Effects on income, health and education in newly connected communities are low. Moreover, the poorest households are lacking funds to get connected. This calls for a stronger focus on electrification through low-cost off-grid technologies, which could improve the cost-benefit balance.
Keywords: 330